ขอบเขตของการประมาณค่าแบบจุดสำหรับปัญหาการจับคู่ - พิจิตร เจริญผล (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
In this project use the Stein-Chen medtod is applied to obtain non-uniform and uniform bounds of pointwise approximation in matching problem by poisson distribution with parameter